ANALISIS RASIO KEUANGAN DALAM MEMPREDIKSI PERUBAHAN LABA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - , Merry Permatasari; , Taufikur Rahman, S.E., M.B.A ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Financial ratio serves to identify the strength and weakness of the finance of a company. Financial ratio allows investors to assess the financial state and operational outcome of the company at present and in the past, as well as serves as a guideline for the investors in making decisions about the investments. The information of financial ratio with regards to the investorsâ interest is in the form of profit information. Profit information is not merely inferred from the profit itself but also from the financial ratio that related with the profit that it may provide prediction of the profit in the future. In addition, as a dependent variable in this research, earning changes use net profit change per future share. In this research, the sample consists of as many as 58 companies during a five-year period for observation (2005-2009). The sample is manufacturing companies that fulfill several criteria of sample selection by using the purposive sampling method. The objective of this research is the empirical evidence on the influence of financial ratios in predicting earning changes in manufacturing companies. The result of this research shows that there are seven variables that are able to predict earning changes significantly, that is, Current Ratio (CR), Gross Profit Margin (GPM), Operating Profit Margin (OPM), Return on Equity (ROE), Ratio Inventory Turn Over (ITO), Basic Earning Power (BEP), and Debt Ratio (DR). Three variables were proved not able to predict earning changes significantly, that is, Net Income to Sales (NIS), Total Asset Turn Over (TATO), and Sales to Current Liabilities (SCL). Current Ratio (CR), Gross Profit Margin (GPM), Operating Profit Margin (OPM), Net Income to Sales (NIS), Return on Equity (ROE), Ratio Inventory Turn Over (ITO), Total Asset Turn Over (TATO), Sales to Current Liabilities (SCL), Basic Earning Power (BEP), and Debt Ratio (DR) simultaneously and significantly affect profit change. The influence of those ten variables to profit change was as much as 19.5%.